THE INFLUENCE OF TEACHING METHODS AND SELF CONFIDENCE ABILITY TOWARDS SCIENCE PROCESS SKILLS AT SD NEGERI 13 KOTA SERANG - Yoma Hatima; Fahrudin Fahrudin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study sought to reveal the influence of teaching methods and self confidence ability towards science process skills. This study was conducted at the fifth grade of SD Negeri Kota Serang. The population was all students of SDN 13 Kota Serang while the samples in this study were the students from class VA and VB SDN 13 Kota Serang. The design of this study design was two-way analysis of variance (ANOVA). The results of this study were (1) there was a difference of science process skills between students who were taught by Discovery methods and students who were taught by Inquiry methods; (2) there was an interaction between teaching methods and students’ self-confidence towards the students’ science process skills; (3) students with high self confidence who were taught by Discovery methods had higher science process skills than those who were taught by Inquiry methods; and (4) students with low self confidence who were taught by Discovery methods had lower science process skills than those who were taught by Inquiry methods.